A new name for Stenus absconditus Tang & Hu, 2018 (Coleoptera, Staphylinidae) - Hu, Cheng-Zhi; Tang, Liang (Zootaxa, 2019)
Stenus absconditus Hu & Tang, 2018 was published in our recent paper, and latter Dr. Alfred Francis Newton kindly informed us that the name was preoccupied by Stenus absconditus Puthz 2017. After confirming the information, we propose a new replacement name for this species.